ISLAMIC PERSPECTIVE ON THE IMPLEMENTATION OF GRAVE ALMS IN KEDUNGSANA VILLAGE, PLUMBON DISTRICT, CIREBON REGENCY - Syafik Muhammad; Huda, Misbahul (CV. Fahr Publishing, 2024)
This research aims to examine the Islamic perspective on the implementation of grave alms in Kedungsana Village, Plumbon District, Cirebon Regency, West Java. With a focus on the understanding and practice of the local community as well as the views of ulama and community leaders regarding the validity and procedures for carrying out the grave alms ceremony. The research method used in compiling this article is using a qualitative descriptive method, with data collection techniques through in-depth interviews and observations to describe facts about the culture of implementing grave alms. Observation results show that grave alms is a traditional celebration as a form of gratitude from the people of Kedungsana Village to the giver of good fortune, namely Allah SWT. Apart from that, grave alms also aim to build social harmony and serve as a reminder that there is nothing permanent and eternal in this world except Allah SWT. The practice of collecting and distributing infaq and grave alms in Kedungsana Village has generally been carried out appropriately and in accordance with the rules applicable in Islamic teachings.